Analysis of boron- and phosphorus-doped diamond layers by glow discharge optical emission spectroscopy in argon and neon. (April 2023) - Weiss, Zdeněk; Ashcheulov, Petr; Lambert, Nicolas; Taylor, Andrew; Lorincik, Jan; Sung, Kil-dong; Davydova, Marina; Mortet, Vincent
Abstract: Boron- and phosphorus-doped diamond layers were analysed by glow discharge optical emission spectroscopy. A methodology for quantitative depth profiling of layers was developed, based on multi-matrix calibration with a calibration model assuming matrix-independent emission yields. Factors affecting accuracy and sensitivity of analysis are discussed. Analysis of boron with the B I line at 208.959 nm yielded a satisfactory performance. Analysis of phosphorus with the P I line at 178.284 nm in an argon glow discharge is affected by an argon-related interference, which can be avoided by using a neon discharge. The use of which leads to an eightfold improvement in the phosphorus detection limit. A light interference effect affecting the analysis in transparent layers is described, indicating that layers are transparent far into the ultraviolet region. Graphical abstract: Samples of B-doped diamond on silicon: the colours are due to thin-film interference, depending on layer thickness. The bright spots are erosion craters after GDOES analysis where the coating was sputtered away and the silicon substrate is exposed. Image 1 Highlights: Quantitative analysis of B- and P-doped diamond layers by Glow discharge optical emission spectroscopy (GDOES) is described. The methodology of the analyses is based on a multi-matrix sputter rate-corrected calibration. The accuracy and the precision of the analyses is discussed, an excellent performance was achieved for boron. There is a Ar line interference at the P line at 178.284 nm. It was avoided by using Ne as the discharge gas instead of Ar. Periodic intensity variations occur in GDOES due to interference of light reflected from the coating and the substrate.